Study of the District Industries Centres Programme - Planning Commission (Planning Commission, 1994)
At the instance of the Planning Commission, the Programme Evaluation Organisation (PEO) undertook the study of District Industries Centres Programme (DICP) with the main objectives of; finding out the extent to which the District Industries Centre (DIC) has been able to provide support and services under 'one roof' to small and village entrepreneurs, assessing the views of the entrepreneurs regarding the working of the DIC, identifying the bottlenecks and shortcomings in the functioning of the programme, and its overall impact on entrepreneurs. Based on these, improvements for making the programme more effective were to be suggested.
Programme Evaluation Organisation Planning Commission (Government of India) New Delhi